Convective drying of sawdust-sludge mixtures: The effect of the sludge matrix. Issue 7 (19th May 2019) - Li, Jie; Wu, Cheng-Wei; Fraikin, Laurent; Salmon, Thierry; Toye, Dominique; Nistajakis, Emmanuel; Léonard, Angélique
Abstract: Thermal drying is an important treatment method for sewage sludge. Sludges from Oupeye, Grosses Battes, and Embourg wastewater treatment plants (WWTPs) were chosen for study. The effect of the mass fraction of sawdust (10%, 20%, 30%, and 40%) on sludge drying in a fixed bed dryer was investigated. A universal testing machine was used to determine the stiffness of the samples. X-ray tomography was employed to measure the structural properties of sample beds including the volume, total exchange surface, and void fraction. Both a lower moisture content of sludge and a higher mass fraction of sawdust lead to higher stiffness. The initial void fraction, bed volume, and total exchange surface of the sample bed are all related to sludge matrix and sawdust addition; however, the maximum drying rate is proportional to the initial total exchange surface, which is independent of the sludge matrix. This proves that sawdust addition is a positive means of sludge drying because of the increase in the initial total exchange surface.